Ética e liberdade em Michel Foucault: uma leitura de Kant - Kraemer, Celso (2008)
The complementary thesis to the doctorate of Foucault about the Anthropology of Immanuel Kant opens some theoretical and methodological perspectives in his work. Among them the present research investigates the possibility of Ethics and the notion of Liberty in Foucault. The guide line that goes throughout the chapters is the lecture of Kant which appears in the minor texts, being the first just the complementary thesis at the beginning of the intellectual career of Foucault, and the last about Kant s Aufklärung at the end of his career. The data treatment attends the procedure of Foucault in the complementary thesis: facing the minor texts with the more canonical ones. In the complementary thesis Foucault related the Anthropology to the Critics of Kant. In the present research the parallels are settled between the minor texts where Foucault deals with Kant in his books, emphasizing Madness and Civilization and The Order of things. The result shows that there are some kantism in Foucault, one can recognize it in the archeology and in the genealogy. The kantian Critic looks to get a new strength in them. This one suffers an actualization by Foucault. Thus, the archeological and genealogical Critic looks for the conditions of possibility of the origin , the duration and the disappearance of different discursive and non-discursive strategies of practices of knowledge-power that he calls historical empiricities. On the other side, the realm of empiricities is signed by Aperture; in it the Truth shows its reciprocal dependency with Freedom. These three realms (Critic, empiricity and Aperture) establish the proper field for the question of ethics and freedom in the immanence of knowledge-power relations. In the game of subjection and autonomy grows the esthetic of existence as art of the self; in this function it requires the care of the self, the know yourself and the practices of the self